Reliability and Validity of Longshi Scale in Assessing the Activities of Daily Living of Patients with Spinal Cord Injury - Miaoling CHEN; Fubing ZHA; Fang LIU; Mingchao ZHOU; Yulong WANG; Jianjun LONG (康复学报)
Objective:To evaluate the reliability and validity of Longshi daily living ability rating scale(Longshi scale)in patients with spinal cord injury, and to provide objective basis for its wide application.Methods:A total of 412 patients with spinal cord injury(SCI)were selected from 60 medical institutions in China for the activities of daily living(ADL)assessment.Each patient was evaluated twice by both professionals(rehabilitation physician or therapist)and non-professionals(family member or companion of the patient).The Longshi scale and Barthel index were used for each assessment, and all assessments were required to be completed within the same day.The intraclass correlation coefficient(ICC)was used to analyze the correlation of scores on Longshi scale in different evaluators; the Kappa test was used to analyze the consistency of ADL rating in different evaluators; Barthel index was used as the criterion, and Pearson correlation analysis was used to evaluate the criterion validity of Longshi scale;and compare the time spent in the evaluation of the two scales.Results:A total of 406 patients completed the scale evaluation effectively, with an effective rate of 98.5%.①The results of reliability test: Kappa test was used to evaluate the ADL level of the Longshi scale by professionals and non-professionals, with k value of 0.878 and 95%confidence interval(CI)of 0.839-0.917, with statistically significant difference(P<0.01).Intraclass correlation coefficient analysis was used to analyse the different of the scores of Longshi scale in different evaluators, with ICC value was 0.836, 95%CI was 0.805-0.863, with statistically significant difference(P<0.01).②The results of validity inspection: the Pearson correlation coefficient r value between the total scores on Longshi scale of the bedridden, domestic, and community groups and Barthel index was 0.711, 0.596 and 0.610, respectively, with statistically significant difference(P<0.001).③The results of time spent evaluation: compared with Barthel index(BI), both professionals and non-professionals took less time to evaluate Longshi scale than Barthel index, with statistically significant difference(P<0.05).Conclusion:The Longshi scale has the advantages of being easy to understand and less time to evaluate.It is good reliability and standard validity in the evaluation of ADL for SCI patients, and it has better feasibility and can be popularized and applied in clinical practice.